Impact of Green Innovation on Organizational Performance: The Mediating Role of Management Commitment and the Moderating Role of HRM Practices - Nelson, Alden; Majesty, Shechah; Setyawan, Agustinus (Indonesian Journal of Sustainability Accounting and Management, 2026)
This study investigates the effects of green innovation on organizational performance, examining the mediating role of management commitment and the moderating influence of Human Resource Management (HRM) practices. Data were collected from 229 respondents in the electronic manufacturing industry and analyzed using PLS-SEM. The results indicate that green innovation exerts a strong positive impact on both management commitment and organizational performance. Furthermore, management commitment significantly mediates the relationship between green innovation and performance. The findings also reveal that HRM practices serve as a crucial moderator, enhancing the impact of management commitment on organizational outcomes. Theoretically, this research contributes to sustainability accounting by redefining it as a managerial obligation that bridges the gap between eco-friendly innovation and firm performance. Strategically, the study suggests that manufacturing firms can maximize the benefits of green innovation by fostering high levels of leadership commitment and implementing robust HRM strategies. This dual approach ensures that environmental initiatives translate into long-term competitive advantages and sustainable growth. Future research should explore these dynamics within larger corporate frameworks to determine if increased firm size further augments the positive outcomes of green innovation and ESG reporting practices.